WANITA ISLAM DI TENGAH PERSIMPANGAN: Sebuah Upaya Mencari Sosok Wanita Islam Modern - Siti Raudhatul Jannah (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2020)
Islam puts women’s rights in high-esteem in all aspects of life and also positioned women equally with their partners, the men. The fixture, figure, and ideal nature of Moslems’ women are not those who are tied eith strict and traditional bond blindly nor the such women who have lost their self-image as happened to the western women. Moslems’ women are those who take parts in all aspects of their very real life, adapt themselves to the advancement of science and technology, realize their position as women, wives, mother and pious Moslem’s-career women.